(untitled) (Experimental biology, 2021)
Juzgun (Latin Calligonum) is a genus of perennial deciduous branched shrubs from the Buckwheat family (Latin Polygonaceae). According to some data, the genus includes up to 158 plants, but since the genus is poorly studied, the definition of the species included in it is considered inaccurate. Moreover, some scientists argue that it is impossible due to multiple morphological differences that do not have geographic definiteness. The chemical composition of plants from the genus Juzgun contains tannins, citric and phenol carboxylic acids, alkaloids, leukoanthocyanidins, flavonoids. We have investigated the chemical composition and identification of biologically active compounds in the plant raw materials of Juzgun white. Physicochemical studies have been carried out. The elemental composition of raw materials has been determined. Were determined the mass fraction of moisture and ash in the raw material.